Disputas sociais na crítica musical jornalística: o potencial polêmico da Folha de S.Paulo - Schoenherr, Rafael (Universidade do Vale do Rio do Sinos, 2005)
This research tries to understand in which way the social disputes are manifestated in the journalistic musical review. Through the investigation of the constituted approach between the musical and the mediatic areas, as well the analyse of the editorial startegies of the Folha de S. Paulo newspaper, in the months from may to june of 2003, it is dicussed in which level a polemic conversation is provided about the contemporary music
Keywords: jornalismo; musica contemporânea; potencial polêmico; crítica musical; journalism; polemic potential; contemporary music; journalist musical review; Ciências Sociais Aplicadas